Multi-ingredient pre-workout supplementation changes energy system contribution and improves performance during high-intensity intermittent exercise in physically active individuals: a double-blind and placebo controlled study - Caique Figueiredo; Fábio Santos Lira; Fabricio Eduardo Rossi; François Billaut; Rodrigo Loschi; Camila S. Padilha (Taylor & Francis Group, 2020)
Background Nutritional ergogenic aids are commonly used to boost physiological adaptations to exercise and promote greater fitness gains. However, there is a paucity of data about multi-ingredient pre-workout supplementation (MIPS). Therefore, the aim of the present study was to investigate the acute effects of MIPS on the oxidative, glycolytic and ATP-CP energy systems contribution, time spent above 90% V̇O2max (T90% V̇O2max), excess post-exercise oxygen consumption (EPOC) magnitude, number of efforts and time to exhaustion during a high-intensity interval exercise (HIIE) session. Methods Twelve physically-active and healthy men completed the HIIE sessions that involved running bouts of 15 s on the treadmill at 120% of the maximum aerobic speed (MAS), interspersed with 15 s of passive recovery. Blood lactate was collected at immediately post, 3, 5, and 7 min post exercise. The contribution of ATP-CP, glycolytic and oxidative systems was analyzed at rest, during the HIIE sessions and for 20 min post. Performance variables (time to exhaustion, number of efforts) and oxygen consumption were also analyzed. Results MIPS significantly increased the number of efforts performed (MIPS: 41 ± 10 vs Placebo: 36 ± 12, p = 0.0220) and time to exhaustion (MIPS: 20.1 ± 6 min vs Placebo: 17 ± 5 min, p = 0.0226). There was no difference between supplements for both T90% V̇O2max (p = 0.9705) and EPOC (p = 0.4930). Consuming MIPS significantly increased the absolute oxidative energy system contribution by 23.8% (p = 0.0163) and the absolute ATP-CP contribution by 28.4% (p = 0.0055) compared to placebo. There was only a non-significant tendency for a higher glycolytic system contribution after MIPS ingestion (p = 0.0683). Conclusion Acute MIPS ingestion appears effective at increasing both aerobic and anaerobic alactic energy contribution and time to exhaustion during a HIIE protocol.